The new Turbo Wing – TW propulsion for VTOL aircraft - Liviu Grigorian GIURCA (INCAS Bulletin)
This paper relates about to a new class of propulsion systems named Turbo Wing- TW for VTOL aircraft (including civil and military drones). The idea behind this concept is to fully integrate a propulsion system into a wing structure, so that the aircraft takes full benefits of the coupling of wing aerodynamics and the propulsion thrust stream.